Improvement of animal welfare in lactating sows reared outdoor in Mediterranean area - Scollo, Annalisa; Cozzi, Giulio; Bondesan, Valerio; Gottardo, Flaviana (Acta Agraria Kaposváriensis, 2010)
The project focused on studying the behaviour of free range sows, to evaluate the level of utilization of different areas inside the paddock (hut, shaded area and wallow) under different climatic conditions. In the study has been also assessed the sows preference towards a certain type of hut. The behaviour of 23 lactating sows, kept outdoors in individual farrowing paddock, were observed in 12 months starting from August in order to monitor it under different climatic conditions. Activities and areas in which these actions were performed were recorded from 8.30 a.m. to 4.30 p.m. for a total of 31 days. Considering the thermal requirements of pigs, the days of observation were divided into three categories: cold (≤15 °C), optimal (from 15 to 25 °C) and hot (over 25 °C). The white hut seem to be preferred by the sow even if the inner temperature is not different from one of the gray. This preference could be due to the length of both sides which allow an easier transition from standing to lying down. haded area seems to be under-exploited, also under hot environment and this is likely due to the insufficient protection from sun radiation. The presence of the wallow seems to positively affect the welfare of sows during hot season anyway other systems of cooling such as sprinkler could be tested in order to reduce the heat stress in outdoor sows reared in the mediterranea area.